2003
DOI: 10.1111/j.1468-3083.2004.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of squamous cell carcinoma treated with topical imiquimod 5%

Abstract: We report the first two cases of squamous cell carcinoma successfully treated with imiquimod 5% cream as a monotherapy. Imiquimod is a new immunomodulating drug that is registered for genital HPV infection but has also shown good efficacy in several cutaneous malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…15,[21][22][23][24][25][26] In this study complete regression was observed in 9 of 12 lesions (75%; 4 Bowen's disease lesions and 5 invasive SCCs) in 8 patients, and partial regression was detected in the remaining 3 lesions (25%; 1 Bowen's disease and 2 invasive SCCs) in 2 patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…15,[21][22][23][24][25][26] In this study complete regression was observed in 9 of 12 lesions (75%; 4 Bowen's disease lesions and 5 invasive SCCs) in 8 patients, and partial regression was detected in the remaining 3 lesions (25%; 1 Bowen's disease and 2 invasive SCCs) in 2 patients.…”
Section: Discussionmentioning
confidence: 93%
“…In previous reports, no recurrence of Bowen's disease lesions and invasive SCCs was detected after a follow-up period varying from 1 to 15 months, and from 1 to 21 months, respectively. [9][10][11][12][13][14][15][16][17][21][22][23][24][25][26] The mechanism of action of imiquimod appears to be complex and is not yet fully elucidated. Imiquimod binds to toll-like receptor 7 on dendritic cells inducing the release of a variety of proinflammatory cytokines (eg, interferon alfa) that in turn stimulate an antitumor immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-treatment complete response was observed in all patients in eight of the studies (comprising 12 patients), [634][635][636][637][639][640][641][642] with histological confirmation of clearance in all but one study. 635 One case report of topical imiquimod use observed no response in one of three foot and lower leg SCCs in the same patient.…”
Section: Topical Imiquimodmentioning
confidence: 99%
“…There was one prospective case series that included three patients with four SCCs, 634 one retrospective case series in which there was one eligible patient with SCC 635 and the remainder were case reports of one or two patients. [636][637][638][639][640][641][642] Outcomes after treatment for these studies are summarised in Table 54.…”
Section: Topical Imiquimodmentioning
confidence: 99%